Effects of Trichoderma-enriched biofertilizer and farmyard manure on the growth and yield of brinjal (Solanum melongena L.) (Dhaka University Journal of Biological Sciences, 2020)
A pot experiment was carried out to assess the comparative effects of Trichoderma-enriched biofertilizer and farmyard manure on the growth and yield components of brinjal (Solanum melongena L.). The treatments were T0 (control), T1 (Trichoderma-enriched biofertilizer 5 t/ha), T2 (Trichoderma-enriched biofertilizer 10 t/ha), T3 (Trichoderma- enriched biofertilizer 15 t/ha), T4 (Farmyard manure 5 t/ha), T5 (Farmyard manure 10 t/ha) and T6 (Farmyard manure 15 t/ha). The experiments were laid out in completely randomized design (CRD) with three replications of each treatment. Among the different treatments T3 showed best as much as twice more effective than farmyard manure in increasing growth and yield parameters (plant height, fruit length, fresh weight and dry weight of stem, leaf and fruit) of brinjal plants. Overall, all the treatments increased macronutrients and micronutrients content and uptake by brinjal plants over control. Analysis of post-harvest soil samples also revealed that all the parameters except pH were increased due to different treatments.Dhaka Univ. J. Biol. Sci. 29(1): 1-8, 2020 (January)